Cyclosporin A in cadaveric organ transplantation. Issue 6268 (21st March 1981) - Calne, R Y; White, D J; Evans, D B; Thiru, S; Henderson, R G; Hamilton, D V; Rolles, K; McMaster, P; Duffy, T J; MacDougall, B R; Williams, R
Abstract : The use of cyclosporin A (CyA) with a protocol designed to avoid the effects of nephrotoxicity resulted in a one-year survival of 86% in recipients of renal allografts from unmatched cadaveric donors. The drug also controlled rejection of liver and pancreatic allografts. It was possible to change patients initially treated with CyA to azathioprine and corticosteroids and vice versa, thus enlarging the potential value of CyA in organ allografting. Of 34 recipients of renal allografts, 29 were currently receiving only CyA as immunosuppressive treatment. Twelve patients never required any adjuvant steroid treatment. These results suggest that CyA is an effective immunosuppressant, and if used with care side effects need not be severe.